(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
The article analyzes the importance of simplified language in the process of delivering medical information to patients and the general public. The principles of conveying complex terms and scientific expressions in a simple, understandable form in medical communication are considered. Also, recommendations are developed for Uzbek medical discourse based on international “plain language” standards. The results of the study serve to increase patients’ knowledge about health, prevent medical errors, and ensure reliable communication between doctors and patients.